1995
DOI: 10.1016/s0006-3495(95)80002-0
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded DNA organization in bacteriophage heads: an alternative toroid-based model

Abstract: Studies of the organization of double-stranded DNA within bacteriophage heads during the past four decades have produced a wealth of data. However, despite the presentation of numerous models, the true organization of DNA within phage heads remains unresolved. The observations of toroidal DNA structures in electron micrographs of phage lysates have long been cited as support for the organization of DNA in a spool-like fashion. This particular model, like all other models, has not been found to be consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…Arrangement of the DNA along the long axis was not considered in earlier theoretical work (Purohit et al, 2005), presumably because it was unclear what global structure would permit this. The folded toroid, first proposed by Nicholas Hud (Hud, 1995) solves this problem.…”
Section: Slightly Elongated Capsids: Simulation Of ϕ29mentioning
confidence: 99%
See 1 more Smart Citation
“…Arrangement of the DNA along the long axis was not considered in earlier theoretical work (Purohit et al, 2005), presumably because it was unclear what global structure would permit this. The folded toroid, first proposed by Nicholas Hud (Hud, 1995) solves this problem.…”
Section: Slightly Elongated Capsids: Simulation Of ϕ29mentioning
confidence: 99%
“…These led to the coaxial spool model (Richards et al, 1973), which remains the most widely-accepted model for DNA in icosahedral capsids. Other models include the ball of string (Earnshaw and Harrison, 1977), the folded chain (Earnshaw and Harrison, 1977), the interwound toroid (Earnshaw et al, 1978), toroidal winding (Kosturko et al, 1979), the kinked chain (Serwer, 1986), and the folded toroid (Hud, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that regions of the packed DNA form domains of parallel fibers, which in some cases have different orientations, suggesting a certain degree of randomness (8,9,13,14). The above observations have led to the proposal of several long-range organization models for DNA inside phage capsids: the ball of string model (13), the coaxial spooling model (8,11,13,14), the spiral-fold model (15), and the folded toroidal model (16). Liquid crystalline models, which take into account properties of DNA at high concentrations and imply less global organization, have also been proposed (9).…”
mentioning
confidence: 99%
“…In the ''mature'' P4 phages (i.e., complete infective particles with capsid and tail), one of the two cohesive ends of the DNA is known to remain anchored near the connector region (19), while the bulk of packed DNA plus its associated water molecules virtually occupy the total volume of the capsid (20). Despite the system's apparent simplicity, the overall arrangement of the DNA inside the viral capsid remains largely unknown (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%